2018
DOI: 10.29196/jubes.v26i6.1005
|View full text |Cite
|
Sign up to set email alerts
|

User Evaluation of Media Technology in the Urban Scene of the City

Abstract: The contemporary development in the field of the digital technology for the media has been witnessed an increasing use in the urban scene of the city. This causes disconnection of the visual references of the place, which are replaced by a simulation of the reality by digital images as an alternative to the physical presence. So, the Availability and spread of the new means of visual communication and information technologies create new symbols of contemporary life, that have different levels of acceptances by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Results showed that increases in the Reynolds number had a greater effect on the gas phases than the liquid phases. The boundary layer thickness in the upstream region of the obstacle decreases with Re rising; however, the recycling zone height increases downstream of the obstacle [24]. Explain how the experimental data was compared with output simulations for a hydraulic jump on a sloping bottom for four different obstacle slopes that end on a horizontal bottom showed the generated slopes of the jump for each one of those at various sites by adjusting the depth of the tail water.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that increases in the Reynolds number had a greater effect on the gas phases than the liquid phases. The boundary layer thickness in the upstream region of the obstacle decreases with Re rising; however, the recycling zone height increases downstream of the obstacle [24]. Explain how the experimental data was compared with output simulations for a hydraulic jump on a sloping bottom for four different obstacle slopes that end on a horizontal bottom showed the generated slopes of the jump for each one of those at various sites by adjusting the depth of the tail water.…”
Section: Introductionmentioning
confidence: 99%